Antoni ebook Let's do dinner. - Porowski, Antoni (2024)
In the follow-up to his New York Times bestseller Antoni in the Kitchen , Queer Eye star Antoni Porowski shares exuberantly easy dinners for every night of the week Let’s Do Dinner  is an invitation into Antoni’s easy kitchen. Dinner with Antoni means satisfying meals full of clean protein and loads of vegetables, with splurges of carbs and decadence. Simple, yes, but always special. Antoni keeps shopping lists short and steps and pans to a minimum.  Pulled chicken nachos, pasta carbonara with scallions and peas, or pan-seared steak with harissa butter and crispy potatoes—it’s all good for post-work evenings or casual entertaining. Antoni shows how to crank the flavor, make exciting suppers from pantry staples, create new takes on classics by swapping in one surprising ingredient, and build a rousingly flavored vegan grain bowl. Plus, he lets you in on the secret weapons in every kitchen that get great food on the table fast.